ANALISIS PENGARUH PRODUKTIVITAS PADI DAN JAGUNG TERHADAP PERTUMBUHAN EKONOMI SEKTOR PERTANIAN (Studi Kasus di Kabupaten Lamongan, Tuban dan Ngawi) - Masruro, Masruro; Subkhania, Nurul (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2025)
This study aims to examine the influence of rice and corn productivity on the economic growth of the agricultural sector in the districts of Lamongan, Tuban, and Ngawi, both partially and simultaneously. The dependent variable in this research is the economic growth of the agricultural sector, while the independent variables are rice productivity and corn productivity. This research employs a quantitative approach with a panel data regression method. The Fixed Effect model is considered the most appropriate. The study uses time series data covering the period from 2011 to 2023, with a cross-section consisting of three regions: Lamongan, Tuban, and Ngawi. The results of this study indicate that rice productivity has a significant positive influence on the economic growth of the agricultural sector, whereas corn productivity has a significant negative influence on the economic growth of the agricultural sector. Collectively, the independent variables of rice productivity and corn productivity significantly affect the dependent variable of agricultural sector economic growth. Keywords: Economic Growth, Productivity, Agricultural Sector.